(untitled) (PANGEEA, 2025)
In Romania there are hundreds of isolated areas with limited access to utilities, most of them being protected natural areas: national and natural parks, Nature 2000 Ecological Network areas for which the biodiversity conservation is a high priority. This article aims to present an environmentally friendly solution for providing energy in protected natural and mountain areas. The developed model is a smart energy system based on increasing the use of energy potential from renewable sources: hydropower, solar energy, wind energy, in an isolated area of Vanatori Neamt Natural Park, Romania, by using low energy power sources to potentiate a higher energy power source. The model allows energy conservation and includes a distribution network. The challenges were to find an optimal solution for energy storage and to minimize environmental impact. The purpose of developing this model was to capitalize renewable energy sources within protected areas in order to secure the electricity needed for those consumers who either cannot be connected to the national energy system or their connection would be very costly or the quality of the provided energy would be very low. Both in the construction phase and in the operational phase, it will not cause any environmental impact, as demonstrated in the Environmental Impact Assessment Study